Poor quality of sleep in patients on chronic hemodialysis - Arache, Wafaa; Laboudi, Fouad; Ouanass, Abderrazzak; El Kabbaj, Driss (Ibnosina Journal of Medicine and Biomedical Sciences, 2019)
Introduction: Sleep disorders (SD) are common in patients with renal failure, particularly in those on dialysis. This can impair their daily quality of life and worsen their cardiovascular prognosis. Objective: Our work aimed to describe the prevalence and risk factors of SDs among chronic hemodialysis patients in the Nephrology and Dialysis Department of the Rabat Military Hospital, Morocco. Patients and Methods: The trial was designed as a prospective single-center study and included all hemodialysis patients in the nephrology department of the Rabat Military Hospital. For each patient, we assessed four SDs: insomnia, sleep apnea, restless legs syndrome, and excessive daytime sleepiness. Results: We included 52 patients; the mean age of the patients was 50 ± 17 year (range 24–76); male:female ratio was 1.1. SDs were found in 40 patients with a predominance of insomnia and sleep apnea syndrome (SAS), and multivariate logistic regression was used to identify factors associated with different SD Insomnia was correlated with anemia, excessive daytime sleepiness, and inflammation; SAS was correlated with age ≥50 years, obesity and excessive daytime sleepiness. Restless legs syndrome was associated with advanced age, excessive daytime sleepiness and presence of a biological inflammatory syndrome. Conclusions: Sleep disorders have a considerable impact on the quality of life of patients on dialysis, so it is essential to look for them and especially to determine the associated factors to control them.
Keywords: Excessive daytime sleepiness; hemodialysis; insomnia; restless legs syndrome; sleep apnea; sleep disorders